Education quality and student satisfaction nexus using instructional material, support, classroom facilities, equipment and growth: Higher education perspective of Pakistan - Ikram, Maryam; Kenayathulla, Husaina Banu (Frontiers in Education, 2023)
Purpose – The primary purpose is to examine the impact between education quality (EQ) and student satisfaction (SS) in terms of instructional materials, support, classroom facilities and equipment, and growth in Pakistani private higher education institutes. Methodology – This study utilised correlation-focused quantitative research by randomly distributing a 54-items questionnaire to 440 postgraduate students in Pakistan’s private higher education institutions (HEIs). SPSS (V.23) and PLS-SEM (V. 3.3.3) were employed to investigate the data. Findings – The findings demonstrate that EQ has a direct and significant positive effect on student satisfaction with instructional materials, support, classroom facilities and equipment, and growth in private higher education institutions. Research implications – The current study will help policymakers, Higher Education Commission (HEC), and institutions to pay greater attention to the significance of education quality indicators in making a difference in higher education, which may contribute to student satisfaction. In addition, their efforts will significantly contribute to the nation’s progress. Furthermore, it will contribute to the betterment of the world by accomplishing the sustainable development goal of quality education set by the United Nations. The recent findings will also have far-reaching advantages for society, demonstrating the positive effects that high-quality education may have on a nation’s progress by creating competent and productive students. Limitations – Only private universities in Pakistan’s higher education sector were considered for this study, and students enrolled in post-graduate degrees were the subjects of this investigation. This study was restricted to testing in Punjab province. Another limitation of this study is that it is based on research framework deduced from previous underpinnings and literature. Originality – These findings contribute to the existing area of research on the direct and significant effects of EQ on SS in HEIs. These findings may positively impact student satisfaction in private higher education institutions. The findings can guide higher education institutions (HEIs) regarding the importance of EQ in achieving desirable student satisfaction (SS). Because the Higher Education Commission (HEC) efforts will contribute considerably to the growth of higher education institutions (HEIs) and the nation, this study is vital for policymakers and practitioners working in higher education.